Analysis of High School Students Mistakes in Completing The Topic Limit Function Type Higher Order Thinking Skill - Sartika, Endang Sri; Maimunah, Maimunah; Hutapea, Nahor Murani (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
The ability to think higher order is one of the curriculum demands that can train students' ability to solve problems and improve their experience in doing HOTS questions.The purpose of this study was to analyze student mistake in solving HOTS-type limit function questions. This research is a qualitative descriptive study, and the subjects of this study consisted of 24 students in class XI consisting of students with high, medium, and low abilities at SMA N 2 Bangkinang Kota. Data collection techniques obtained from tests and documentationhe analysis technique carried out involves grouping students based on high, medium, and low abilities. Based on the results and discussion, this study shows that there are three types of student errors: comprehension errors, transformation errors, and skill errors. Factors of student error in solving HOTS questions In the function limit problem, students have not been able to absorb information well, they have not been able to understand the meaning of the questions given, and they are not careful and less thorough in the process.